1987
DOI: 10.3109/00016488709107338
|View full text |Cite
|
Sign up to set email alerts
|

Subsets of tonsillar lymphocytes and activated cells in each subset analysed by Two-color flow cytometry

Abstract: We analysed subsets of tonsillar lymphocytes and activated cells in each subset by two-color flow cytometry. There were many helper T cells (CD 4+ leu 8-) and few inducer T cells (CD 4+ leu 8+) in the tonsil. The situation was the reverse in the peripheral blood. The tonsil had few suppressor T cells (CD 8+ CD 11+). The proportion of activated cells (HLA-DR+) was low in the peripheral blood and high in the tonsil. In the tonsil, the ratio of cells with transferrin receptors to total lymphocytes was higher in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…T lymphocytes purified from human tonsils are mainly CD4 cells (Sugiyama et al, 1976(Sugiyama et al, , 1984(Sugiyama et al, , 1987Plum et al, 1987), CD8 T cells being proportionally less numerous in tonsils than in the peripheral blood (Sugiyama et al, 1987). The prevalence of CD4 cells in tonsils suggests that tonsillar T lymphocytes are functionally oriented to helper activity (Sugiyama et al, 1987). Several immunohistochemical studies have revealed the existence of tonsillar T cells expressing the CD57 antigen characteristic of cells with NK activity (Okada et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…T lymphocytes purified from human tonsils are mainly CD4 cells (Sugiyama et al, 1976(Sugiyama et al, , 1984(Sugiyama et al, , 1987Plum et al, 1987), CD8 T cells being proportionally less numerous in tonsils than in the peripheral blood (Sugiyama et al, 1987). The prevalence of CD4 cells in tonsils suggests that tonsillar T lymphocytes are functionally oriented to helper activity (Sugiyama et al, 1987). Several immunohistochemical studies have revealed the existence of tonsillar T cells expressing the CD57 antigen characteristic of cells with NK activity (Okada et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Tonsils were classified on the basis of clinical and pathohistological diagnoses in HT and RT according to Sugiyama et al [5]. After excision, the specimens for enzyme detection were immediately frozen.…”
Section: Tissue Specimensmentioning
confidence: 99%